The Mythic Hero's Appearance in the Twelve Seasons of Nature : His Dramatic Action in Literature and Film. - Eriksson, Edward (The Edwin Mellen Press, 2012)
The hero in literature and film is an expression of seasonal occurrence. His behavior exhibits, symbolically, the relationship of the sun to the earth in twelve phases. It begins at the March equinox and proceeds through the natural year. He assumes, then, twelve distinct characterizations. His conflicts and successes reflect the natural conditions of Early Spring, Mid-Spring, Late Spring, and so on. It creates an aesthetic development that primarily converts traditional mythic dynamics (based in agriculture) into story lines. His character in a given season suggests the dynamism of that seaso.